Analyzing the Influence of Artificial Intelligence on Digital Innovation: A SmartPLS Approach - Harfizar; Wicaksono, Muhammad Wisnu; Hakim, Miftah Baidhowi; Wijaya, Fadly Hadi; Saleh, Taufikurrahman; Sana, Eirene (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2024)
This study investigates the influence of Artificial Intelligence (AI) on digital innovation using a SmartPLS approach, drawing insights from a dataset comprising 156 relevant observations. In the rapidly evolving digital landscape, AI has emerged as a powerful driver of innovation, reshaping organizational processes and outcomes across various sectors. Through a comprehensive analysis, the research explores the intricate relationships between AI adoption and digital innovation outcomes, addressing key questions regarding the extent to which AI influences process efficiency, product quality, and service creativity. The findings reveal significant correlations, highlighting the role of AI in enhancing organizational readiness, technological integration, and data quality. Moreover, the study identifies the critical importance of fostering an innovation culture and implementing effective change management strategies to leverage the full potential of AI-driven digital transformation. The robustness of the SmartPLS model is confirmed through substantial R-Square values and path coefficients, affirming the validity of the research hypotheses. Overall, this research contributes to a deeper understanding of the mechanisms through which AI influences digital innovation, offering actionable insights for businesses, policymakers, and researchers seeking to navigate and harness the potential of AI-driven digital transformation.